Physical Literacy Development of Elementary Students in Physical Education Classes - Aisyah Dini Nuraryati; Adi S (Indonesian Journal for Physical Education and Sport, 2025)
The reduction of physical activity among children continues to be a major concern globally, including in Indonesia. The purpose of this study is to analyze physical literacy in upper-grade elementary students (V and VI) from SD Negeri Cepoko and SD Negeri Sadeng 01, Semarang City, employing a descriptive quantitative survey method. The study employed a total sampling method, involving 89 participants. Physical literacy was assessed across three domains: physical competence (measured through TIAMSA, PACER, and Sit-Up tests), motivation and self-confidence, as well as knowledge and understanding. The results revealed that most students were classified as progressing, with only a quarter reaching the achieving category. At SD Negeri Cepoko, all students were categorized as progressing, whereas in SD Negeri Sadeng 01, a number of students particularly male students in grade V and female students in grade VI reached the achieving level. These results highlight disparities in physical literacy outcomes between schools and student groups. Hence, improvements in PJOK learning strategies, teacher development, and supportive learning environments are required to encourage sustainable participation in physical activity.